Jimmy, Sinclair, and Jim: on the biographical trail of James Sinclair Ross - John J. O'Connor (Ilha do Desterro)
The deaths of Earle Birney and Robertson Davies late in 1995 reminded readers of Canadian literature that the old order—those writers born before the First World War—was quickly passing. Of the major figures born in the early years of this century (Birney, Davies, Callaghan, MacLennan, Ross), only Ross was still living at the beginning of 1996, albeit in very poor health in a nursing home in Vancouver.